An integrated approach for tracking climate-driven changes in treeline environments on different time scales in the Valle d'Aosta, Italian Alps. (October 2021) - Masseroli, Anna; Leonelli, Giovanni; Morra di Cella, Umberto; Verrecchia, Eric P; Sebag, David; Pozzi, Emanuele D; Maggi, Valter; Pelfini, Manuela; Trombino, Luca
Both biotic and abiotic components, characterizing the mountain treeline ecotone, respond differently to climate variations. This study aims at reconstructing climate-driven changes by analyzing soil evolution in the late Holocene and by assessing the climatic trends for the last centuries and years in a key high-altitude climatic treeline (2515 m a.s.l.) on the SW slope of the Becca di Viou mountain (Aosta Valley Region, Italy). This approach is based on soil science and dendrochronological techniques, together with daily air/soil temperature monitoring of four recent growing seasons. Direct measurements show that the ongoing soil temperatures during the growing season, at the treeline and above, are higher than the predicted reference values for the Alpine treeline. Thus, they do not represent a limiting factor for tree establishment and growth, including at the highest altitudes of the potential treeline (2625 m a.s.l.). Dendrochronological evidences show a marked sensitivity of tree-ring growth to early-summer temperatures. During the recent 10-year period 2006–2015, trees at around 2300 m a.s.l. have grown at a rate that is approximately 1.9 times higher than during the 10-year period 1810–1819, one of the coolest periods of the Little Ice Age. On the other hand, soils show only an incipient response to the ongoing climate warming, likely because of its resilience regarding the changeable environmental conditions and the different factors influencing the soil development. The rising air temperature, and the consequent treeline upward shift, could be the cause of a shift from Regosol to soil with more marked Umbric characteristics, but only for soil profiles located on the N facing slopes. Overall, the results of this integrated approach permitted a quantification of the different responses in abiotic and biotic components through time, emphasizing the influence of local station conditions in responding to the past and ongoing climate change.